Functional Properties of Cell-Seeded Three-Dimensionally Woven Poly(ε-Caprolactone) Scaffolds for Cartilage Tissue Engineering - Moutos, Franklin T. (Mary Ann Liebert, Inc., 2010)
Articular cartilage possesses complex mechanical properties that provide healthy joints the ability to bear repeated loads and maintain smooth articulating surfaces over an entire lifetime. In this study, we utilized a fiber-reinforced composite scaffold designed to mimic the anisotropic, nonlinear, and viscoelastic biomechanical characteristics of native cartilage as the basis for developing functional tissue-engineered constructs. Three-dimensionally woven poly(ɛ-caprolactone) (PCL) scaffolds were encapsulated with a fibrin hydrogel, seeded with human adipose-derived stem cells, and cultured for 28 days in chondrogenic culture conditions. Biomechanical testing showed that PCL-based constructs exhibited baseline compressive and shear properties similar to those of native cartilage and maintained these properties throughout the culture period, while supporting the synthesis of a collagen-rich extracellular matrix. Further, constructs displayed an equilibrium coefficient of friction similar to that of native articular cartilage (μ(eq) ∼0.1–0.3) over the prescribed culture period. Our findings show that three-dimensionally woven PCL–fibrin composite scaffolds can be produced with cartilage-like mechanical properties, and that these engineered properties can be maintained in culture while seeded stem cells regenerate a new, functional tissue construct.